What does research on disability inclusion at University of Cape Town reveal regarding strategies to achieve inclusion? - Karisa, A.; Nseibo, K.; McKenzie, J. (South African Journal of Higher Education, 2024)
Universities have historically had ableist leanings that exclude people with disabilities. Yet, people with disabilities have a right to attend institutions of higher education, as does everyone else. What is called for is that institutions transform towards disability inclusion. The purpose of this article is to use the case study of research conducted at University of Cape Town (UCT) to suggest strategies for disability inclusion in institutions of higher education. The research question was: What does research carried out at UCT on disability inclusion related to staff, students, and curriculum tell us about strategies that have been used to achieve inclusion, the effectiveness of these strategies and what recommendations can be made for increasing the level of disability inclusion and equity at UCT? A scoping review of the literature on disability inclusion at UCT was conducted. Selected literature was thematically analysed based on the research question and aligned to the strategic goals of UCT. Four emergent themes are presented: including disability in the decolonial discourse, collaborating to enhance disability inclusion, enhancing disability inclusive social responsiveness, and other strategies to enhance systemic change towards disability inclusion. UCT has made significant strides to include students with disabilities, yet there is much still to be achieved. Disability inclusion in institutions of higher learning is not only about ensuring accessibility, but is also about addressing how disability is understood and how it is included in the curriculum.